2020
DOI: 10.1186/s12904-020-00660-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the experience of caregiving at end of life or in hastened death: a narrative synthesis review

Abstract: Background End-of-life caregiving frequently is managed by friends and family. Studies on hastened death, including aid in dying or assisted suicide, indicate friends and family also play essential roles before, during, and after death. No studies have compared the experiences of caregivers in hastened and non-hastened death. The study aim is to compare end-of-life and hastened death caregiving experience using Hudson’s modified stress-coping model for palliative caregiving. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 66 publications
(273 reference statements)
0
30
0
Order By: Relevance
“…Despite these challenges, the expectation of impending death and shortened duration of caregiving in the context of hastened death may result in less caregiver burden. [20] One study found no significant difference in depression, grief, or mental health service use between caregivers whose loved ones requested assisted dying and those whose loved ones did not. However, those whose loved ones received a lethal prescription were more likely to believe that their loved one's choices were honored and less likely to have regrets about how their loved one died.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, the expectation of impending death and shortened duration of caregiving in the context of hastened death may result in less caregiver burden. [20] One study found no significant difference in depression, grief, or mental health service use between caregivers whose loved ones requested assisted dying and those whose loved ones did not. However, those whose loved ones received a lethal prescription were more likely to believe that their loved one's choices were honored and less likely to have regrets about how their loved one died.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inadequate knowledge and information also affected family caregivers’ perception of being in control and their ability to make advanced care plans, as findings revealed feelings of uncertainty as well as ambivalence among caregivers following the making of EOL decisions. End-of-life caregiving requires new knowledge and mindset because the duration of end-of-life caregiving facilities learn new skills or gain confidence in abilities and certainty in decision making [ 17 ]. Previous studies have revealed that making decisions to accept or reject life-sustaining treatments for family members are seen as difficult and stressful [ 18 , 19 , 20 , 21 ], as “non-resuscitation” is often perceived as “giving up” [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 Even in early stages of precontemplation, family/friends can already start shouldering a heavy burden. 7 43 Schutt 31 explored the framing of MAiD under either a biomedical or palliative lens. Biomedical decisionmaking focuses on the individual and the treatment.…”
Section: Values and Decision-makingmentioning
confidence: 99%
“…The focus of MAiD is often on the patient, although family/friends are the ones who bereave, whether they were supporters or not of MAiD. Previous research suggests improved bereavement with MAiD due to the opportunity for closeness, saying goodbye, or copreparing for end of life (EOL) 5–7. Nonetheless, with a limited number of jurisdictions permitting MAiD, factors such as social isolation, stigma or religious acceptance can impact the expression of grief and bereavement 8 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation